Responsibility of the Land Assessor for the Results of the Assessment in Land Procurement - Ameliyani, Riza; Laturette, Adonia Ivonne; Latupono, Barzah (PAMALI: Pattimura Magister Law Review, 2026)
Introduction: The process of assessing land acquisition for the public interest by the appraisal whose price is then deliberated and determined as the value of the amount of compensation, but there is a lack of transparency in determining the amount of compensation by the appraisal. Where appraisal is an independent institution.Purposes of the Research: The purpose of this article is to review and analyze the form of land appraiser's accountability in assessing land values for public interest.Methods of the Research: This study uses normative legal research. As primary legal materials, namely the 1945 Constitution of the Republic of Indonesia, Law Number 5 Number 1960 concerning the Basic Agrarian Law, Law Number 2 of 2012 concerning Land Acquisition for Development in the Public Interest, Government Regulation Number 19 of 2021 concerning the Implementation of Land Acquisition for Development in the Public Interest, Government Regulation Number 39 of 2023 concerning the Implementation of Land Acquisition for Development in the Public Interest.Results Main Findings of the Research: This study concludes that the legal force of the results of the public appraiser's assessment report in land acquisition for public interest is final, meaning that the government and/or agencies that require land owned by the community pay according to the assessment results and close the space for deliberation regarding the amount and quantity, limited to deliberation regarding the form of compensation (Article 31 paragraph 1 and Article 34 of Law Number 2 of 2012). Meanwhile, the responsibility of land appraisers in assessing land values that are not in accordance with the principles of land acquisition that can harm one party and cause disputes between the parties involved in it can be subject to administrative sanctions and/or criminal sanctions.